Developing a Barcode-Based Dice Card Game to Improve Descriptive Writing Skills in Elementary School - Astutik, Puji; Supriyono, Supriyono; Rachmiazasi Masduki, Lusi (STAI Miftahul Ula Nganjuk, 2025)
This development research is motivated by the critical need to foster writing skills, a foundational literacy mandate outlined in the Independent Curriculum and Law No. 20 of 2003 on the National Education System. Descriptive text writing, in particular, is a fundamental competency in elementary-level Indonesian language learning that often presents challenges for students. Addressing these challenges requires innovative learning media that not only meets cognitive objectives but also creates interactive, engaging, and contextually relevant learning experiences for students in the digital age. In response, this study aims to develop and test the effectiveness of a Barcode-Based Dice Card Game, named GARDU, in improving students' descriptive writing skills. The research employed the Research and Development (R&D) method, following the Borg & Gall model, combined with a Quasi-Experimental design. The population consisted of third-grade students from SDN Songgokerto 01 and SDN Songgokerto 03 in Batu city, with a sample of 52 students divided into experimental and control groups. Data were collected using validation sheets, observation sheets, user response questionnaires, and descriptive writing performance tests (pre-test and post-test). The results from material and media experts validated the GARDU media as